Athletes as heroes and role models: an ancient model. Issue 1 (2nd January 2017) - Reid, Heather
Abstract: A common argument for the social value of sport is that athletes serve as heroes who inspire people – especially young people – to strive for excellence. This argument has been questioned by sport philosophers at a variety of levels. Not only do athletes seem unsuited to be heroes or role models in the conventional sense, it is unclear more generally what the social and educational value of athletic excellence could be. In this essay, I construct an argument for the social and educational value of sport built upon the relationship between athletes, heroes, and the song culture that celebrated them in ancient Greece. On this model, athletes are neither heroes nor role models in the conventional sense. Rather, athletes, athletics, and the poets who extolled them were part of a cultural conspiracy to celebrate and inspire virtue (aretē) by connecting a community with its heroic past. Festivals such as the Olympic Games, but also local events such as funeral games, educated and unified communities by cultivating an aesthetic appreciation for virtue and by inspiring youth to strive for it. Ancient athletes were not heroes, rather they re-enacted heroic struggles, thereby experiencing heroic virtues, and inspiring both artists and spectators to bond with the higher ideals implied by their shared belief in divine ancestry. In this way, athletes, athletics, and the media that celebrated them played important social and educational roles. Insofar as modern sport performs a similar service, its association with heroism and with moral education may ultimately be justified.